A pilot study investigating the influence of dietary boron levels on osteoporosis in postmenopausal women - Rababah, Taha; Aludatt, Muhammad; Gammoh, Sana; Salameh, Feras Bani; Magableh, Ghazi; Almajwal, Ali; Yucel, Sevil; AL-Rayyan, Yara; AL-Rayyan, Numan (WILEY, 2024)
This study aimed to evaluate the impact of dietary boron on osteoporosis in postmenopausal Jordanian women. Sixty-six women diagnosed with osteoporosis were recruited and data on personal information, dietary habits, medical history, and lifestyle were collected. Bone mineral density, serum calcium, and serum vitamin D measurements were obtained from patient records. This study showed a strong correlation between boron intake and bone mineral density in these women with osteoporosis and a negative correlation between boron intake and serum calcium (p .05). A significant link was found between boron intake and bone mineral density highlighting the importance of nutritional and lifestyle factors affecting bone health. Further research on the specific impact of boron is warranted to better inform dietary interventions for osteoporosis prevention and management.
Keywords: bone; boron; calcium; diet; osteoporosis; postmenopausal women; VITAMIN-D; BORIC-ACID; PHYSICAL-ACTIVITY; BONE-DENSITY; RISK-FACTORS; TOOTH LOSS; SUPPLEMENTATION; ASSOCIATION; FRACTURES; Food Science & Technology